2002
DOI: 10.1108/02652320210451214
|View full text |Cite
|
Sign up to set email alerts
|

Estimating customer defection in personal retail banking

Abstract: Using Juster’s probability scale, this study examines a sample of 881 customers’ self‐reported estimates of probable defection from their main bank. One year later these customers’ statuses with their main bank were reviewed, allowing comparison of intended with actual defection. This methodology allows not only investigation of the Juster scale’s performance in a “subscription” type market but also identification of those customers with a predisposition to switch banks. Bank management can then decide if and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 19 publications
2
56
0
2
Order By: Relevance
“…Retail banking financial products has been broadly classified under the following headings: transaction and payment products, such as cheque accounts and debit cards; investment products, such as savings accounts, fixed deposits and unit trusts; credit and borrowing products, such as credit cards, home loans, overdrafts and car finance; and financial planning products such as retirement annuity plans and education policies. Garland (2002) observed that retail banks usually operate on a long-term ''cradleto-grave'' customer management strategy. This means that some customers may be regarded as being unprofitable in the short terms but become profitable over time (see also Trubik and Smith 2000).…”
Section: Service Strategy Of Nigerian Retail Banksmentioning
confidence: 98%
“…Retail banking financial products has been broadly classified under the following headings: transaction and payment products, such as cheque accounts and debit cards; investment products, such as savings accounts, fixed deposits and unit trusts; credit and borrowing products, such as credit cards, home loans, overdrafts and car finance; and financial planning products such as retirement annuity plans and education policies. Garland (2002) observed that retail banks usually operate on a long-term ''cradleto-grave'' customer management strategy. This means that some customers may be regarded as being unprofitable in the short terms but become profitable over time (see also Trubik and Smith 2000).…”
Section: Service Strategy Of Nigerian Retail Banksmentioning
confidence: 98%
“…Customer defection is explained as a critical situation where customers leave and abandon a service provider and opt for another (Garland, 2002). Similarly, customer defection rate had been explained to be the degree to which customers terminate the relationship they have had with businesses over a period (Page et al, 1996).…”
Section: Customer Defection Groups Reasons For Their Defections Andmentioning
confidence: 99%
“…Customer defection occurs when customers switch between service providers in the service environment (Garland, 2002). It can be total or partial (Stewart, 1998;Colgate and Hedge, 2001).…”
Section: Switching Intentionsmentioning
confidence: 99%
“…According to Dibb and Meadows (2001), relationship marketing has been one of the best approaches that are probable to meet with a lot of interest with respect to switching behavior. When customers abandon one service provider for another it means customer switching or swapping (Garland, 2002). Complete or fractional understanding can exist as explained by Stewart, 1998;Colgate and Hedge, 2001.…”
Section: Introductionmentioning
confidence: 99%